Variations of work engagement and psychological distress based on three working modalities during the COVID-19 pandemic - Unda-López, Alejandro; Paz, Clara; Hidalgo-Andrade, Paula; Hermosa-Bosano, Carlos (Frontiers in Public Health, 2023)
With the onset of the COVID-19 pandemic, the rapid spread of the SARS-COV-2 virus became a global health threat affecting people’s mental and physical health, as well as working conditions and modalities. The reorganization of the work environment also affected work engagement and psychological distress levels. This manuscript assesses how work engagement and distress vary according to gender and age across three working modalities. We used a voluntary response sampling strategy to collect data on psychological distress and work engagement between August 2021 and January 2022. Results are from 542 people working in Ecuador during the COVID-19 pandemic. Overall, participants experienced psychological distress; women and younger participants presented higher psychological distress. Regarding engagement, the sample showed average levels of total engagement, average levels of vigor, and high levels of dedication and absorption. Men presented higher levels of total work engagement and vigor. Psychological distress was significantly and negatively correlated with total work engagement scores and its three factors. There were no differences in work engagement according to the different modalities. However, teleworkers reported significantly higher levels of psychological distress than hybrid workers. Findings are discussed considering ideas for decision-makers to explore the benefits of flexible working practices.